An Exploration of Patient Navigation and Community Health Worker Activities Across National Comprehensive Cancer Control Programs - Elizabeth A. Rohan; Renee McDougall; Julie S. Townsend (Health Equity, 2018)
Purpose: Health disparities persist across the cancer care continuum. Patient navigator (PN) and community health worker (CHW) interventions are designed to increase health equity. National Comprehensive Cancer Control Program (NCCCP) awardees develop and implement plans to coordinate cancer prevention and control activities, including supporting PN and CHW interventions. This content analysis examined NCCCP action plans to assess the extent to which jurisdictions report engaging in PN and/or CHW activities. Methods: We abstracted PN and CHW content from NCCCP action plans and coded content according to specific areas of PN and/or CHW intervention (e.g., screening, survivorship, and cancer type), used descriptive statistics to characterize overall results, and calculated chi-squares to determine whether programs engaged PNs and CHWs differently. Results: Eighty-two percent (n=53) of 65 NCCCP action plans had content related to PN and/or CHW activities, with more PN language (83%) than CHW (58%). These action plans described engaging PNs and CHWs in activities across the cancer continuum, but particularly for screening (60%) and survivorship (55%). Eighty-one percent of these plans described activities related to workforce development, such as training and standardizing roles and competencies. Programs engaged CHWs more often than PNs for outreach and in community settings. Conclusion: The majority of NCCCP awardees reported engaging in PN and/or CHW activities. Understanding how NCCCP awardees engage PNs and CHWs, including awardees' needs for workforce development in this area, can help Centers for Disease Control and Prevention provide more focused technical assistance as programs increase engagement of PNs and CHWs to improve health equity.